STUDI EVALUATIF PERAN HAKIM AD HOC dALAM PENYELESAIAN PERSELISIHAN HUBUNGAN INdUSTRIAL dI PENGAdILAN HUBUNGAN INdUSTRIAL YOGYAKARTA - Wijayanta, Tata Wijayanta; Hernawan, Ari (Yustisia, 2014)
AbstractThe research aim to evaluate the role of ad hoc judges in the settlement of industrial relation disputes, as well as to explore further what are the obstacles which may occur in the course of performing their duties. The research is a normative-empiric legal research. The data research comes from secondary data derived from literature studies and primary data from field researches. The data analyzed by qualitatively. The results of this research will show that ad hoc judges are appointed by the Supreme court and assigned to cases by the President of the court of Industrial Relations. Since its establishment, there has only been two appointments of ad hoc judges (one from the enterpreneur and the other from the labor union), and the court has tried and decided upon 104 cases (2006-2011). The most paramount obstacle turns out to be the lack of knowledge of the ad hoc judges in civil procedural laws while trying and deciding cases before them.Keywords: court of Industrial Relations, Ad hoc JudgeAbstrakPenelitian ini bertujuan untuk mengevaluasi peran hakim ad hoc dan untuk mengkaji hambatan-hambatan yang dialami hakim ad hoc dalam penyelesaian perselisihan hubungan industrial di Pengadilan Hubungan Industrial (PHI). Penelitian ini merupakan penelitian hukum empiris bersumber pada data sekunder dan data primer melalui penelitian kepustakaan dan penelitian lapangan Data dianalisis secara kualitatif. Hasil penelitian menunjukan bahwa hakim ad hoc diangkat oleh Mahkamah Agung dan ditunjuk dalam suatu perkara oleh Ketua PHI. Sejak didirikan PHI yogyakarta hanya terdapat dua hakim ad hoc yang masing-masing merupakan perwakilan dari pengusaha dan pekerja. Sebanyak 104 perkara diperiksa dan diputus oleh PHI yogyakarta antara 2006-2011. Hambatan utama yaitu kurangnya pengetahuan dan pemahaman hakim ad hoc tentang hukum acara perdata yang menghambat ketika para hakim ad hoc ini harus memeriksa dan memutus perkara.Kata kunci:  Pengadilan hubungan industrial, Hakim ad hoc